2017
DOI: 10.3343/alm.2017.37.3.231
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Resistance to Extended-Spectrum Cephalosporins, Fluoroquinolone, and Carbapenem in Gram-Negative Bacilli and the Emergence of Carbapenem Non-Susceptibility in Klebsiella pneumoniae: Analysis of Korean Antimicrobial Resistance Monitoring System (KARMS) Data From 2013 to 2015

Abstract: BackgroundNational surveillance of antimicrobial resistance becomes more important for the control of antimicrobial resistance and determination of treatment guidelines. We analyzed Korean Antimicrobial Resistance Monitoring System (KARMS) data collected from 2013 to 2015.MethodsOf the KARMS participants, 16 secondary or tertiary hospitals consecutively reported antimicrobial resistance rates from 2013 to 2015. Data from duplicate isolates and institutions with fewer than 20 isolates were excluded. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 24 publications
4
67
0
1
Order By: Relevance
“…While we did not analyze pathogens isolated from other sites, we identified a significant increase in the antimicrobial resistance rate to broad-spectrum antibiotics of bloodstream pathogens isolated at the study hospital. Consistent with our findings, the Korean Antimicrobial Resistance Monitoring System (KARMS), comprising a total of 35 secondary and tertiary care participating hospitals, reported that the antimicrobial resistance rate of E. coli and K. pneumoniae to broad-spectrum antibiotics has been increasing [17]. According to the KARMS, the E. coli and K. pneumoniae resistance https://doi.org/10.3904/kjim.2017.332…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…While we did not analyze pathogens isolated from other sites, we identified a significant increase in the antimicrobial resistance rate to broad-spectrum antibiotics of bloodstream pathogens isolated at the study hospital. Consistent with our findings, the Korean Antimicrobial Resistance Monitoring System (KARMS), comprising a total of 35 secondary and tertiary care participating hospitals, reported that the antimicrobial resistance rate of E. coli and K. pneumoniae to broad-spectrum antibiotics has been increasing [17]. According to the KARMS, the E. coli and K. pneumoniae resistance https://doi.org/10.3904/kjim.2017.332…”
Section: Discussionsupporting
confidence: 85%
“…35, No. 3, May 2020 rates to FQs were 30% in 2004, increasing to 42% and 34%, respectively, in 2013 [17]. Similarly, the E. coli and K. pneumoniae resistance rate to cefotaxime were 10% and 30%, respectively, in 2004, increasing to 29% and 40%, respectively, in 2013 [17].…”
Section: Discussionmentioning
confidence: 97%
“…A limitation of this study was that we used ceftazidime in ASC, which could result in the low detection of CTX-M-14 type because the hydrolysis of ceftazidime is lower than that of cefotaxime with this CTX-M type. We could not detect carbapenem-resistant K. pneumoniae; although the prevalence of carbapenem-resistant Enterobacteriaceae (CRE) is still low in Korea [18], the recent sharp rise in CRE caused by carbapenemaseproducing Enterobacteriaceae (CPE) has created challenges for infection control in Korea [19]. K. pneumoniae is the most common bacterial type of CPE, carrying various types of carbapenemases, such as K. pneumoniae carbapenemase, New Delhi metalloβ-lactamase, and OXA-type carbapenemases [20].…”
mentioning
confidence: 79%
“…of group 1 and CTX-M-14 of group 9 [17], triggers more usage of last options for the treatment resulting in vicious antimicrobial resistance. In South Korea, cefotaxime resistance reached at 38% for E. coli and at 35% for K. pneumoniae clinical isolates in 2015 [18] and it was associated with dominance of both CTX-M-15 and -14 since the mid-2010s [19]. The enterobacterial blood isolate collection of seven-month-period in 2017 presented cefotaxime resistance rates at 31.6% for E. coli and at 24.0% for K. pneumoniae, which were less than those in 2015, probably due to the differed specimens and surveillance systems.…”
Section: Continuing Increase In Ctx-m-type Esbl-producingmentioning
confidence: 99%